1973
DOI: 10.1111/j.1476-5381.1973.tb17252.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 and the bovine sphincter pupillae

Abstract: Summary1. The bovine isolated sphincter pupillae incubated in Krebs solution releases a biologically active substance tentatively identified as prostaglandin E2. 2. The prostaglandin did not appear to be of neural origin or to result merely from tissue degeneration.3. The spontaneous release of prostaglandin E,-like material was related to the tone of the sphincter. Output increased as tone was acquired after setting up the tissue and fell when various procedures were used to reduce the tone. 4. Low concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
3

Year Published

1973
1973
1989
1989

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 21 publications
2
14
0
3
Order By: Relevance
“…An effect on acid secretion seems somewhat unlikely, but a hypothesis, apart from others such as the back-diffusion of hydrogen ions through a damaged mucosa (Davenport, 1965), is that PG release has a vasodilator role in gastric blood vessels (Eckenfels & Vane, 1972). PGs seem to generate muscle tone in some tissues which are contracted by PGE compounds (Posner, 1971;Bennett & Posner, 1971;Ferreira, Herman & Vane, 1972), and since PGE and A compounds produce vasodilatation, an inhibitory role is possible in blood vessels. Work on the kidney provides direct evidence for this view (McGiff, Crowshaw, Terragno, Lonigro, Strand, Williamson, Lee & Ng, 1970;Aiken & Vane, 1971), and the cerebral and conjunctional vasoconstriction produced by indomethacin provides indirect evidence (Sicuteri, Michelacci, Anselmi, 1965;Vecchio & Fontana, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…An effect on acid secretion seems somewhat unlikely, but a hypothesis, apart from others such as the back-diffusion of hydrogen ions through a damaged mucosa (Davenport, 1965), is that PG release has a vasodilator role in gastric blood vessels (Eckenfels & Vane, 1972). PGs seem to generate muscle tone in some tissues which are contracted by PGE compounds (Posner, 1971;Bennett & Posner, 1971;Ferreira, Herman & Vane, 1972), and since PGE and A compounds produce vasodilatation, an inhibitory role is possible in blood vessels. Work on the kidney provides direct evidence for this view (McGiff, Crowshaw, Terragno, Lonigro, Strand, Williamson, Lee & Ng, 1970;Aiken & Vane, 1971), and the cerebral and conjunctional vasoconstriction produced by indomethacin provides indirect evidence (Sicuteri, Michelacci, Anselmi, 1965;Vecchio & Fontana, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…The bullock iris sphincter preparation contains a PGE-sensitive contractile system which is blocked by SC 19220 (Posner, 1973). Our recent studies (Dong & Jones, 1982) have revealed that iloprost, a stable and potent mimetic of PGI2 (Casals-Stenzel et al, 1983) (Figure 1), possesses remarkably high agonist activity on the iris preparation and appears to behave as a partial agonist at the PGE receptor.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast the bullock iris sphincter is more responsive to PGE2 than PGF2. (Posner, 1973). We decided to characterize further the PGE-sensitive system in the bovine iris sphincter, with a view to comparing it with other smooth muscle preparations responsive to PGE2 and related analogues.…”
Section: Introductionmentioning
confidence: 99%